Children’s Rights Fulfillment in Families of Female Migrant Workers: An Islamic Law Perspective from Aceh Tenggara - Noor Fadillah Hayatusyifa; Fakhrurrazi M. Yunus; Aulil Amri; Manuel Beltrán Genovés; Nur Syahirah Binti Mohammad Nasir (Yayasan Cendekia Gagayunan Indonesia, 2026)
The increasing participation of women as migrant workers has created complex socio-legal consequences within family structures, particularly concerning the fulfillment of children's rights. While economic remittances from female migrant workers contribute to improving household welfare, the prolonged physical absence of mothers raises critical concerns regarding parenting, emotional attachment, and moral development of children. Existing studies largely focus on the economic benefits of labor migration, while limited attention has been given to the holistic fulfillment of children's rights from an Islamic legal perspective. This study aims to examine the fulfillment of children's rights in families of female migrant workers in Bukit Tusam District, Southeast Aceh Regency, and to analyze the issue through the framework of Islamic law. The research employs an empirical qualitative approach through field research, with data collected via in-depth interviews, observation, and documentation involving female migrant worker families, substitute caregivers, and community stakeholders. The findings indicate that children's economic and formal educational rights are relatively fulfilled through remittances and continued access to schooling. However, the rights related to parental care, emotional support, and moral-religious guidance are often inadequately addressed due to the absence of maternal caregiving. From the perspective of Islamic law, the fulfillment of children's rights requires a holistic approach grounded in the principles of maqāṣid al-sharīʿah, particularly the protection of lineage, intellect, and welfare. This study contributes to the discourse on Islamic family law by emphasizing the need for integrative policies and community-based support systems to ensure the comprehensive protection of children's rights in migrant worker families.